PENGARUH CAREER PATH DAN AMBIGUITAS PERAN TERHADAP KINERJA KARYAWAN PT WIJAYA ANUGERAH CIPTA OPTIMA - Lestari, Silfiana Dian; Emi, Emi (Universitas Muhammadiyah Tangerang, 2021)
ABSTRACT This study’ aims to determine the contribution of Career Path and Role Ambiguity to Employee Performance at PT Wijaya Anugerah Cipta Optima. The independent variables are Career Path And Role Ambiguity, while the dependent variables is Employee Performance . This study uses a quantitative approach. The sample used in this study was 55 respondens using a random sampling method from all the labor population at PT Wijaya Anugerah Cipta Optima. The method used is a quantitive method. Primary data collection was obtained from the distribution of quesionnaires and secondary data obtained from agencies. The results of this study indicate that Career Path (X1) and Role Ambiguity (X2) contribute positively to the performance of employee (Y) of PT Wijaya Anugerah Cipta Optima. Career Path And Role Ambiguity Together contribute to Employee Performance Keywords: Career Path, Role Ambiguity, Employee Performance.